An Overview of Studies on the Influence of Domestic Verbal Violence on Children Personality Development - Meng, Qingliang (Advances in Social Sciences Research Journal, 2024)
An increasing number of adolescents are experiencing psychological problems in China, which has affected their personality development. An overview of studies on the influence of domestic verbal violence on children personality development was made, followed by a comparison between the status-quo of the existing studies of the U.S.A. and China. Results indicate that one cause for children personality development problems may lie in parents’ ignorance of the effect of verbal violence. The paper also reveals scarce studies have been done to explore the effect of domestic verbal violence on child personality development, thus calling for more attention from both researchers and parents.